2020
DOI: 10.47197/retos.v38i38.75724
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias de afrontamiento como intervención al estrés en futbolistas (Coping strategies as a stress intervention in soccer players)

Abstract: El objetivo de este estudio fue medir los niveles de estrés antes y después de una intervención psicológica centrada en el desarrollo de estrategias de afrontamiento e identificar si esas diferencias fueron estadísticamente significativas en una muestra de futbolistas semiprofesionales. La selección de la muestra fue no probabilística en donde participaron 22 futbolistas varones de 14 a 23 años de edad en el estudio diagnóstico. En el análisis de datos inferencial, se utilizó una prueba no paramétrica t de Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…The closest thing has been the use of seminars to prepare students for what is going to be found in the room using audiovisual media [ 47 ]. In our case, we opted for the visualization technique as a coping strategy to lower anxiety levels with a possible positive impact, other studies having shown decreases in the anxiety generated by competition between young players [ 74 ] and, furthermore, that visualization technique sessions led to observations of academic performance improvement and reduced anxiety about evaluation tests [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The closest thing has been the use of seminars to prepare students for what is going to be found in the room using audiovisual media [ 47 ]. In our case, we opted for the visualization technique as a coping strategy to lower anxiety levels with a possible positive impact, other studies having shown decreases in the anxiety generated by competition between young players [ 74 ] and, furthermore, that visualization technique sessions led to observations of academic performance improvement and reduced anxiety about evaluation tests [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…A simple screening regarding motivation and fear of re-injury can help to identify those players who may have a lower adherence to rehabilitation and thus, a higher risk of worse evolution and subsequent RTP. Additionally, the implementation of psychological interventions such as Cognitive Behavioural Therapy, EMDR or Mindfulness, as well as specific strategies such as motor imagery, relaxation or goal setting (Lope & Solís, 2020;Olmedilla & García-Mas, 2023;Pastora-Bernal et al, 2021), would complement conventional rehabilitation protocols, which generally focus on physical and functional recovery of the knee. Such interventions could help football players to reduce pain perception and kinesiophobia, while improving their mood, perception of social support and optimal psychological readiness for RTP.…”
Section: Limitations Future Lines Of Research and Practical Implicationsmentioning
confidence: 99%
“…Al igual que en nuestra investigación, donde los mayores valores de las variables dependientes cursaron con una disminución de la efectividad laboral, los mayores niveles de AE y AR provocaron una disminución del rendimiento en diversas pruebas atléticas (Gutiérrez-Calvo et al, 1997). Por otro lado se ha comprobado que la inclusión de programas de entrenamiento reducen los niveles de ansiedad, tensión, depresión, riesgos psicosomáticos, aportando implicaciones prácticas para la mejora de la salud psicológica de jóvenes deportistas (Lope Fernández & Solís Briceño, 2020), y adultosmayores (Araque-Martínez et al, 2020), lo cual puede ayudar como forma positiva a amortiguar los efectos de la ansiedad y provocar un efecto contrario que ayude a los sujetos a una mejora en su rendimiento al reinterpretar los síntomas de ansiedad positivamente.…”
Section: General Emergencia Deportistasunclassified
“…Para combatirlos, se establece el trabajo de técnicas de autocontrol (conocimiento del material y protocolos; prácticas de autocontrol y desensibilización a situaciones de riesgo, etc.) (Rotger, 1994),estrategias de afrontamiento (Angehrn, Krakauer, & Carleton, 2020;Lope Fernández & Solís Briceño, 2020;Piñar-Navarro et al, 2020) y en especial hacer hincapié en el mantenimiento de una buena forma física, como partes fundamentales (Araque-Martínez, Ruiz-Montero, & Artés-Rodríguez, 2020;Rotger, 1994).…”
Section: Introductionunclassified